“The New State That We Are Building”: Authoritarianism and System-Justification in an Illiberal Democracy - Lönnqvist, Jan-Erik; Szabó, Zsolt Péter; Kelemen, László (Frontiers in Psychology, 2021)
The Authoritarian Personality, published in 1950 introduces the authoritarian personality, which is characterized by unquestioning obedience and respect for authority. System justification theory (SJT) argues that people are motivated to defend, bolster, and justify aspects of existing social, economic, and political systems. Commitment to the status quo is also a key characteristic of the authoritarian personality. Adorno et al. (1950) argued that the social context matters for how an underlying latent authoritarian character is expressed. This means that authoritarian regimes could be expected to lead to increased authoritarianism and stronger system-justification. We investigated this hypothesis in two representative samples of Hungarians, collected before (2010) and after (2018) eight years of Fidesz’ rule (N = 1000 in both samples). Moreover, the strong version of SJT argues that members of disadvantaged groups are likely to experience the most cognitive dissonance and that the need to reduce this dissonance makes them the most supportive of the status quo. This argument dovetails nicely with claims made by the political opposition to Fidesz, according to which Fidesz is especially popular among low-status members of society. We found that measures assessing authoritarian tendencies did not change between 2010 and 2018. However, more specific beliefs and attitudes did change, and these effects were especially pronounced among Fidesz supporters. Their belief in a just world and a just system has grown stronger, while their attitudes towards migrants had hardened. Low status was associated with lower levels of system-justifying ideologies. However, low status Fidesz voters justified the system more than high status opposition voters in 2018, lending some support for the strong version of SJT. Our results suggest that beliefs and attitudes of Hungarians have changed between 2010 and 2018, and that political leadership played a crucial role in this.